A Novel Method to Investigate the Effect of Social Network "Hook" Images on Purchasing Prospects in E-Commerce. (30th October 2017) - Smaoui, Mohamed R.
Abstract : Background . Social network visual shopping trends are growing e-commerce at unprecedented levels. Images are used as product marketing material; however, image posts are triggering very low consumer behavior and low sales conversion. Objective . To explore how online stores can increase the purchasing prospects of their products using images on social networks. Methods . We introduce a theoretical probabilistic model to estimate consumer behavioral intention and purchasing prospect on social networks, outline parameters that can be exploited to increase click-rate and conversion, and motivate a new strategy to market products online. The model explores increasing online stores' sales conversion by utilizing a product collection landing page that is marketed to consumers through a single "Hook" image. To implement the model, we developed a novel technological method that enabled online stores to post different "Hook" images on social networks and hyperlink them to the product collection landing pages they created. Results . Stores and marketers developed four types of "Hook" images: themed-collaged product images, single product images, lifestyle images, and model images. Themed-collaged product images accounted for 60% of consumer traffic from social network sites. Moreover, consumer purchasing click rate increased at least twofold (4.94%) with the use of product collection landing pages.